Analysis of Owner Requirements of Purse Seine Vessel 180 GT for Fishing Activities on Fishing Line III-Fisheries Management Area (FMA) 572 - Mei Edi Prayitno; Marimin; Taryono Prayitno; Sugeng Hari Wisudo (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Fish resources in FMA 572 have not been managed optimally, especially small pelagic species of 82,573 tons. These waters with high wave conditions of 0.2 – 6 meters are located around the waters of West Aceh, the West Indian Ocean of Aceh, the waters of Nias–Sibolga, the waters of the Indian Ocean–West Lampung, and the Sunda Strait. The purpose of this study was to analyze the owner requirements for 180 GT purse seine vessels as a basis for planning the ship's technical specifications. The research method using a single case study with research respondents is purposive sampling. The research findings explain that the Ship dimension is around 35 meters, the Service velocity of 8 knots, the propulsion system is I line engine model, the auxiliary engine system is a dual-engine model, the Fish storage system uses Cargo hold freezer system, and Fishing aids using Fish Aggregating Devices (FADs) and light lamps, Total crew of 27 Personnel, Fish detection equipment using fish finder equipment, Fishing gear pulling with winch mechanical and power block and the ship's operating time 50 days as well. To increase productivity, it is recommended to standardize purse seine vessels with modern equipment to improve fuel efficiency, and ship crew and reduce ship production costs, so that the price of ships is affordable for fishery business actors.